The Measurement of Macroeconomic Price Level Changes - Ludwig von Auer (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2009)
Textbooks of macroeconomics regularly remind their readers that they should not interpret the macroeconomic price variable as some sort of average price. Instead it represents some price index indicating the average of the individual items price changes between the period considered and some base period. The Laspeyres and the Paasche index are cited as the best known examples of this approach. The present study challenges this tradition. It develops the family of generalised unit value indices. They do not average the individual items price changes but relate the average price of the period considered to that of the base period. It is shown that a wide range of index formulas can be interpreted in this way, including the Laspeyres and the Paasche index. The study also provides an axiomatic comparison between the generalised unit value indices and several traditional price indices (e.g., Laspeyres index, Paasche index, Fisher index).
Keywords: C43; E31; E52; 330; Index Theory; Inflation; Unit Value; Measurement